The functional roles of 3D heterostyly and floral visitors in the reproductive biology of Turnera subulata (Turneroideae: Passifloraceae) - Rech, André Rodrigo; Achkar, Marina Teixeira [UNESP]; Jorge, Leonardo Ré; Armbruster, W. Scott; Almeida, Odair J.G. (Elsevier, 2020)
Heterostyly is a floral polymorphism that reduces conflicts between sexual functions (sexual interference), such as self-pollination in self-incompatible flowers and loss of pollen to incompatible stigmas. In many distylous pollination systems, there is a remarkable structural fit between the stigmas of each morph and the part of the pollinator body where compatible (disassortative) pollen is deposited. Nevertheless, inter-morph pollen transfer is often asymmetrical, with short-styled flowers (S-morph) receiving less compatible pollen than long-styled flowers (L-morph). One way to reduce the problem of sexual interference in short-styled flowers is to place stigmas outside of the flower centre, as seen in three-dimensionally (3D) heterostylous flowers. Heterostyly in Turnera has been extensively studied; however, 3D heterostyly has not been previously reported in this genus. The aims of this study were: 1) to elucidate the pollination system of T. subulata; and 2) to assess whether 3D heterostyly promotes disassortative pollination and reduces self-pollination in short-styled flowers in this taxon. The study population of Turnera subulata exhibited an isoplethic (1:1) ratio, with two well-defined morphs, and a high floral accuracy index for both morphs. Results from an experiment in which we manipulated the 3D orientation of the style showed that compatible crosses were favoured by the 3D flower morphology, consistent with a high floral accuracy. Our results also demonstrate the functional importance of 3D heterostyly in reducing intramorph pollination, as it increases the amount of cross pollen reaching the S-morph flowers. Our results provide the first observation of the presence of 3D heterostyly in this well-studied species and demonstrate the importance of this kind of morphological specialization in ensuring efficiency in an ecologically generalized pollination system.
Keywords: Disassortative pollination; Floral accuracy; Generalized pollination system; L-morph flower; S-morph flower